Absence of Pseudomonas syringae pv. actinidiae in kiwifruit leaves and flowers from Buenos Aires Province, Argentina - Sánchez, María Clara (2017)
Argentina has around 1000 ha of kiwifruit orchards in Buenos Aires Province. This country is recognized as free of Pseudomonas syringae pv. actinidiae (Psa). In 2013, the National Sanitary Service (SENASA) imposed measures to avoid the entrance of this pathogen to the kiwifruit production areas. In this way, a vigilance plan was established and the introduction of plant material was regulated. In March 2015, three infected samples with Psa were detected in orchards at the South-East of Buenos Aires Province and they were immediately eradicated by SENASA. The objective of this work was to identify the bacteria associated with kiwifruit leaf spots and flower blights in commercial orchards of Actinidia deliciosa ‘Hayward’ at Buenos Aires Province, during the 2015-2016 growing season. On spring and autumn seasons, plant tissues were collected from a 100 ha area located in the North and South-East of this Province. Bacterial isolates were obtained from flowers and leaves by tissues mashing and inoculation on nutrient agar supplemented with 5% sucrose (NSA). The primary identification of isolates was performed by biochemical and physiological tests. To confirm their identity, duplex-PCR tests were performed, including negative and positive controls (no template and Psa DNA, respectively). From symptomatic and asymptomatic samples, 120 bacterial isolates were obtained. Thirty of these isolates were morphologically similar to Psa, forming white-creamy, convex, domed and mucoid colonies on NSA. Also, all of them were Gram-negative, produced a green fluorescent pigment on King’s B medium and their metabolism was aerobic. However, none of these strains examined produced any bands following the amplification by PCR with Psa specific primers. Our results show the absence of Psa in the analyzed samples. Further studies are needed to identify these non-Psa bacteria associated with kiwifruit leaf spots and flower blights.